KAUSATIF MORFOLOGI DALAM BAHASA GORONTALO - Fitriyani; Agus Subiyanto; M. Suryadi (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The purpose of this research is to analyze the causative morphology in Gorontalo using a typological approach. This research was conducted using qualitative methods, data were obtained from speakers of Gorontalo language who were listened to and recorded by researchers for analysis so as to obtain the required morphological causative sentences. The results of the study show that there are several affixes which indicate the existence of a morphological causative construction. This affix consists of prefixes, suffixes, and also infixes. In the prefix category there are prefixes ma-, mopohu-, lo-, mopi-, hemo-, moqo-, and hemopo-. In the category of suffixes, there is the suffix -lo, and in the category of infixes, there is the infix -il-. Keywords: causative, affix, Gorontalo language